ANALISA PEMURNIAN GARAM DENGAN METODE HIDRO EKSTRAKSI BATCH DAN KONTINUE DI KABUPATEN JENEPONTO - Nurhikmah Wahab (Universitas Fajar, 2020)
Indonesia is an archipelago with a coastline of 95,181 km and sea area of around 5.8 million km2 or 70% of the total area of Indonesia. Salt production is one of the national issues of concern to the government at this time. Salt farmers in Jeneponto Regency, especially in Bangkala Subdistrict still produce traditional salt with technology that is still very simple (traditional), causing low salt quality. This study aims to (1) find a salt purification method that can be applied in Indonesia to improve the quality of salt in Jeneponto Regency, (2) To analyze levels of salt purity using samples of community salt produced in the Jeneponto area, and (3) to be able to utilize people's salt for further processing into products with higher selling value. The stages of the research method are the process of salt purification by continuous and batch hydroecraction methods, making crystallization of salt purification, drying the salt resulting from the purification crystallization using an oven, dissolving samples of the results of crystallization of purification of salt with a size of -30 mesh, 18-30 mesh, and 10-18 mesh mesh for analysis. Analyze the salts resulting from purification by determining the levels of NaCl, Ca and Mg using the titration process. Methods that meet the requirements of the SNI industry standard salt are found in the batch hydrolysis process method at -30 mesh sieve size in 30 minutes by obtaining values of 98.97% NaCl, Ca 0.084%, and 0.051% Mg content.